Review on Highway Construction Equipment Management: Maximizing Efficiency and Cost Control in Highway Construction (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Construction industry rapidly increases day by day for the smooth operation of construction activity number of construction equipment is required on construction sites .The construction equipment‘s are high in rate their purchase capital in largely consumed the money of any construction company . Therefore their the productivity plays very valuable role because it affect the benefit margin of company .also the effective control on operating cost is required For this effective equipment management is successfully implemented on site As the array of useful equipment expand, the importance of careful planning and operation of construction equipment‗s increases. Fleet achievement of practiced fleet is compared with optimized fleet against equipment idle period per cycle, cost and productiveness.